Jak określić potrzeby językowe pracowników w miejscu pracy - Sobkowiak, Paweł (Neofilolog, 2019)
Globalization of business and use of English in corporations as lingua franca has resulted in growing demand for Business English courses in the workplace. This article tries to present a concise profile of an adult language learner in a broader context of adult education and the implications for the Business English classroom. The claim is made that if we want to provide tailormade courses for employees in companies a thorough analysis of their language needs should be carried out first. Explicitly discussed here are the types of adult learner needs in the business context and the methodology which may be employed in determining them.